As implicações das concepções de qualidade e avaliação na Agenda 2030 da UNESCO e da OCDE: intervenção e consentimento na Base Nacional Comum Curricular - Nogueira, Juliana Maria Teixeira (2024)
This research investigates the implications of the concepts of quality and evaluation of education in the 2030 Agenda of the Organization for Economic Cooperation and Development (OECD) and the United Nations Educational, Scientific and Cultural Organization (UNESCO), as identified in the National Common Core Curriculum. The documents analyzed originate from the main multilateral agencies that discuss the 2030 Agenda, such as UNESCO and the OECD. The research is qualitative, based on bibliographical and documentary research, and aims to answer the following question: what are the implications of the concepts of quality and evaluation of education present in the OECD and UNESCO Agenda 2030, and how are they interpreted and incorporated into Brazilian Basic Education, particularly in the BNCC? The specific objectives aims to contextualize the production of Agenda 2030 as a result of the economic and social relations that constitute world capitalism; to historicize the relations between the OECD and UNESCO and Brazil in the formulation of educational policies; to investigate the categories of quality and educational assessment present in Agenda 2030 based on these documents, and how they are interpreted and incorporated into the BNCC document. This research was motivated by an interest in studying the influences of multilateral organizations on education, given that, according to the theoretical framework of the research, this dynamic is presented as a relationship of intervention and consent between the recommendations of these organizations and educational policies. Therefore, through this summary analysis of documents published between 2015 and 2021, it was possible to understand that these Agenda 2030 documents announce as their main conceptions the quality and evaluation of education based on the development of competencies and skills aimed at sustainability and the challenges of the 21st century, thus revealing a set of individualistic conceptions of learning and sociability, which seek to preserve the social order delegated to the capital valuation.